Karl der Grosse. Charlemagne. - Wengler, Gabriele; Krause, Robert; Weber, Christoph; Papadopoulos, Sandra; Wüst, Alexander, 1973-; Matić, Peter; Fritsch, Regina, 1964- (Taglicht Media ; PreTV, 2013)
The elaborately staged documentary-drama 'Charlemagne' recounts the dramatic, violent and bawdy life of the Middle Ages' most important emperor: his life as a political strategist, a passionate lover, a man that conquered most of Europe and a cultural visionary.